Effect of Sodium Salicylate on the Viscoelastic Properties and Stability of Polyacrylate-Based Hydrogels for Medical Applications - Zuzana Kolarova Raskova; Martina Hrabalikova; Vladimir Sedlarik (International Journal of Polymer Science)
Investigation was made into the effect exerted by the presence of sodium salicylate (0–2 wt.%), in Carbomer-based hydrogel systems, on processing conditions, rheological and antimicrobial properties in tests against Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacterial strains, and examples of yeast (Candida albicans) and mould (Aspergillus niger). In addition, the work presents an examination of long-term stability by means of aging over one year the given hydrogels at 8°C and 25°C. The results show that 0.5 wt.% NaSal demonstrated a noticeable effect on the hydrogel neutralization process, viscosity, and antimicrobial properties against all of the tested microorganisms. The long-term stability studies revealed that hydrogels can maintain antimicrobial activity as well as viscosity to a degree that would be sufficient for practical use.